Application of the Direct Quadrature Method of Moments for the modelling of the enzymatic hydrolysis of cellulose: II. Case of insoluble substrate. (31st July 2016) - Lebaz, Noureddine; Cockx, Arnaud; Spérandio, Mathieu; Liné, Alain; Morchain, Jérôme
Abstract: In the second part of this study, the Population Balance Model developed for the enzymatic hydrolysis of cellulose polymer chains is extended to particulate cellulose substrates. In this case, the particle fragmentation process is complex. This phenomenon is induced by the hydrodynamic shear stress when the particle cohesion is lower than the hydrodynamic force. The particle cohesion depends on the mechanical properties of the substrate particles which are affected by the Endoglucanase (EG) activity that hydrolyses accessible glycosidic bonds all along the reaction. These two effects are taken into account in the model. The Exoglucanase (CBH) activity is assimilated to an erosion process as for soluble substrates. The β -glucosidase activity as well as the inhibition effect are also considered in the global population balance-based model. The numerical resolution of the Population Balance Equation (PBE) is based on the Direct Quadrature Method of Moments (DQMOM) coupled with the Maximum Entropy (ME) reconstruction technique. Numerical results in different cases show coherent prediction of the Particle Size Distribution (PSD) evolution during the hydrolysis reaction as well as the kinetics of simple sugars release. The modelling procedure is supported by experimental data which reveal the importance of the particles cohesion and its evolution during the hydrolysis reaction.